Relative age effects among Malaysian elite adult field hockey players - Hamizi, M. I. F. M.; Low, J. F. L. (International Journal of Human Movement and Sports Sciences, 2022)
Relative age effect (RAE) has been identified as a contributing factor that could affect the chances of an individual attaining elite athletic level. The aim of this study was to identify the presence of RAE among adult Malaysian field hockey players. Birth dates of both men (n=270) and women (n=197) players were obtained from the official website of the 2020 national hockey competition and analyzed for significant differences in the distribution of their birth months using Chi Square Goodness of Fit test. Players' birth months were distributed according to four quartiles. Presence of RAE was found for both men and women categories. Similar results were shown among the men's semifinalists and those who were selected to the national team. However, no RAE was found in the women's semi-finals teams as well as those who were selected to the national team. Suggested reason for the absence of RAE among the more skillful women players could be a lack of competition for places in the team and possibly due to a high turnover of players. Another reason posited was that the relatively younger players were able to persevere and overcome the selection bias, more with their technical and tactical skills than physical advantage.